Implementation of adomian polynomials in variational iteration method for solving volterra integral equations - Ayati, Zainab; Biazar, Jafar; Zareii, Sajedeh (Global Journal of Mathematical Analysis, 2014)
In this paper Adomian polynomials are employed is solving Variational Iteration Method for finding Volterra integral equations. The proposed technique involves Adomian Polynomials in the correction functional equation. The solutions have been found by suggested iterative scheme without any discretization, linearization, or restrictive assumptions, and it is quite efficient and is practically well suited. Two examples are given to verify the reliability and the efficiency of this method. Keywords: Variational Iteration Method, Adomian Polynomials, Volterra Integral Equations, Functional Equation.